O papel do Design na divulgação da ciência: O Projeto Animando o Ano da Luz - Horta, Anderson Antonio; Emar de Almeida , Délcio Julião; Alvarenga Pinto Cotrim , Michelle; Alessi de Carvalho Lafetá, Júlio César; da Conceição Ribeiro , Rita Aparecida (InfoDesign, 2022)
The article presents the perspective of the use of the tools of the Design for the scientific divulgation for children from the project "Animating the Year of the light: the design presents the astronomy for children", developed by the Grupo de Pesquisa Design e Representações Sociais da Universidade do Estado de Minas Gerais and financed by the Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG). His proposal is to combine the specific knowledge about Astronomy to the processes of symbolic construction of Design adapting them to the languages ​​and communications that allow to present a universe of the knowledge of science in a playful way. The methodology used sought to promote the interface between the teaching and learning processes, with the playful nature of the devices created by the design. The methodological processes include a bibliographical reference survey, a study of communication needs and the design of the material and workshops for its dissemination.